Trace elements’ reference levels in blood of breeding black-browed albatrosses Thalassarche melanophris from the Falkland Islands - Furtado, Ricardo (2020)
Trace elements' concentration in the ocean is fast growing and is a source of major concern. Being charismatic and at the top of food chains, seabirds are often used as biological monitors of contaminants. We studied the concentration of trace elements in blood of black-browed albatross from the Falklands Islands, which we here show, by tracking with geolocators, forage over most of the Patagonian Shelf. Levels of trace elements were measured in males and females from two different islands. Blood concentrations of trace elements were not significantly different between islands, which is consistent with observations from foraging behavior revealing that birds from both islands foraged in broadly the same areas in the months before sampling. Arsenic and selenium concentrations in females were higher than in males. Sex-related differences in the concentration of these elements may be related to unknown slight differences in diet or to differences in assimilation between sexes. These results provide reference values for monitoring elemental contamination in the Patagonian Shelf Large Marine Ecosystem using black-browed albatrosses, one of the most abundant top predators and a suitable sentinel for the region's environmental health.